"I’m strong within myself": Gender, class and emotional capital in childcare - Andrew, Yarrow (British Journal of Sociology of Education, 2015)
Emotions have received increasing attention in educational circles in the last decade. Drawing on Bourdieu, feminist scholars use emotional capital to illustrate the ways gendered inequalities can compound the disadvantages of social class. This paper examines relationships within childcare services in Australia, showing how emotional capital functions as a resource for staff. Data from interviews with childcare staff illustrate key aspects of emotional capital, such as reflexivity, resilience and embodiment. Findings show that investing in emotional capital is the key to a long-lasting commitment to childcare work, and should be valued accordingly. © 2013 Taylor & Francis.
Keywords: 2000 à aujourd'hui; 2010-2019; australie; capital émotionnel; care; discipline; maternité; océanie; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; service de garde; sociologie; thématiques; travail; travail du care

Stability and transformation in gender, work, and family: Insights from the second shift for the next quarter century - Blair-Loy, Mary; Hochschild, Arlie; Pugh, Allison J.; Williams, Joan C.; Hartmann, Heidi (Community, Work and Family, 2015)
Arlie Hochschild's The second shift: Working families and the revolution at home argued that the revolution toward gender equality in the USA has been stalled due to three factors: (1) women continue to do most of the ‘second shift’ – the unpaid work of childcare and housework; (2) insufficient flexibility in the workplace for accommodating family caregiving needs; and (3) a deficit of public sector benefits, such as paid parental leave. Since the book's publication in1989, many aspects of the gender structure (how gendered opportunities, barriers, and cultural meanings are socially structured in the USA) remain the same. Yet many aspects have changed. This article looks at areas of stability in the gender structure and areas of transformation in the past quarter century. We then plumb the book for the analytical insights it generates for scholars today. We discuss how deep-seated cultural understandings of gender infuse all levels of analysis: macro-level policies, family and work institutions, and personal experiences of gender, intimacy, and moral commitments. These insights help illuminate paths forward for new research on how new economic developments, including economic insecurity, flexibilization (the increasingly reliance on temporary and contract labor), and the widening social class divide, continue to affect intimacy at home. © 2015 Taylor & Francis.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; discipline; double journée de travail; histoire et politique; inégalités hommes-femmes; maternité; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; sociologie; soins aux enfants; thématiques; travail; travail domestique; états-unis